Role of Human Mesangial-Tubular Crosstalk in Secretory IgA-Induced IgA Nephropathy - Junjun Zhang; Ruwen Zhou; Yiming Mi; Zhangsuo Liu; Bo Huang; Ruxue Guo; Panfei Wang; Songxia Quan; Yali Zhou (Karger Publishers, 2021)
Background: IgA nephropathy (IgAN) is characterized by the mesangial deposition of pathogenic IgA. We previously detected the deposition of pathogenic secretory IgA (SIgA) in the mesangium of about one-third of IgAN patients. Tubulointerstitial injury has an important role in the development of IgAN. However, the relationship between SIgA and tubulointerstitial damage is currently unclear. In this work, the role of the mesangial-tubular crosstalk was explored in the tubulointerstitial damage in SIgA-induced IgAN. Methods: SIgA deposition in renal tissues of IgAN patients was detected by immunofluorescence. Flow cytometry was used to assess the binding of SIgA to human renal mesangial cells (HRMC) and human proximal tubule epithelial (HK-2) cells. HK-2 was co-cultured with HRMC added with SIgA isolated from patients or normal volunteers. Protein synthesis and gene expressions of TNF-α, TGF-β1, and MCP-1 were determined by ELISA and PCR, respectively. The expressions of the above cytokines in renal tissues of patients and normal controls were detected by immunohistochemistry. Results: Twenty-nine of 96 patients had SIgA deposition in the mesangium, but SIgA was rarely detected in the tubulointerstitium. The binding rate of SIgA to HK-2 (2.79%) was significantly lower than that of HRMC (81.6%) (p < 0.001). The expressions of TNF-α, TGF-β1, and MCP-1 in HRMC were significantly higher than in SIgA-stimulated HK-2 (p < 0.05), and their expressions were significantly higher in the SIgA-stimulated co-culture group compared with SIgA-stimulated HRMC (p < 0.05). The expressions of the above cytokines were mainly detected in tubulointerstitium of IgAN patients with positive and negative SIgA deposition, without significant difference between the 2 groups, but to a significantly higher level than that in normal controls, and their expressions positively correlated with tubulointerstitial injury. Conclusion: Inflammatory factors released from the mesangium after SIgA deposition might mediate tubulointerstitial damage via mesangial-tubular crosstalk in IgAN.